Micropulse Cyclophotocoagulation: Initial Results in Refractory Glaucoma. Issue 8 (August 2017) - Emanuel, Matthew E.; Grover, Davinder S.; Fellman, Ronald L.; Godfrey, David G.; Smith, Oluwatosin; Butler, Michelle R.; Kornmann, Helen L.; Feuer, William J.; Goyal, Swati
Abstract : Purpose: The purpose of this study is to evaluate the use of micropulse transscleral cyclophotocoagulation (MP-TSCPC), a new and increasingly popular treatment, in patients with uncontrolled glaucoma. Methods: A retrospective chart review was performed for all patients who underwent a MP-TSCPC at the Glaucoma Associates of Texas. Results: A total of 84 eyes were treated with MP-TSCPC in this study with a mean follow-up time of 4.3 months. The mean age of treated patients was 74 years and 48 (57%) were female. Preoperatively, mean intraocular pressure (IOP) was 27.7 mm Hg and mean number of ocular antihypertensive medications used was 3.3. Mean postoperative IOP at months 1, 3, 6, and 12 were lowered to 16.3 mm Hg (41.2% reduction), 14.6, 13.0, and 11.1 mm Hg, respectively. Postoperative ocular antihypertensive medication use was also lowered to 1.9, 2.0, 2.0, and 2.3 medications at months 1, 3, 6, and 12, respectively. Five patients required further laser or surgical intervention for adequate IOP control. Complications included hypotony, IOP spike, hyphema, serous choroidal detachment, persistent inflammation, and vision loss. At 3 months, inflammation was still present in 46% of eyes and vision loss of at least 1 line was present in 41% of eyes. Conclusions: MP-TSCPC is effective at lowering IOP and decreasing the need for ocular antihypertensive medications. Eyes with limited visual potential or at high risk for incisional glaucoma surgery can successfully be treated with MP-TSCPC as a reasonable and effective alternative to traditional CPC. These results present short-term data and both longer follow-up and further studies are necessary.